Eclectic approach to anxiety disorders among rural children [Abordagem eclética a transtornos de ansiedade em crianças de zona rural] - Ahmadi, Atefeh; Mohamed Sharif, Mustaffa; Ali Akbar, Haghdoust; Syed Mohamed Shafeq, Mansor (Sociedade de Psiquiatria do Rio Grande do Sul, 2017)
Introduction: Anxiety disorders in primary school-aged children negatively affect their mental health and psychological development. Available non-medical treatments for these conditions are time-consuming and expensive. In this context, eclectic therapy is a therapeutic approach that incorporates some therapeutic techniques and philosophies to create the ideal treatment. In this study, eclectic therapy consisted of art therapy and cognitive-behavioral therapy designed for children suffering from high level of anxiety in their middle childhood years. The therapy also included group guidance sessions for their mothers. The effectiveness of this intervention was examined in the study. Methods: 61 students aged 9-12 years with high levels of anxiety participated in the study. Intervention A (n = 20) consisted of 9-hour eclectic therapy for children with 3-hour group guidance sessions for their mothers. Intervention B (n = 20) consisted of 9-hour eclectic therapy for children. There was also a control group (n = 21). Results: Teacher ratings of children’s mental health difficulties and self-report ratings of anxiety disorders indicated a significant difference from pretest to posttest, revealing a large effect size between the two interventions. Higher levels of pretest scores significantly predicted higher posttest scores for all domains of anxiety and mental health difficulties. Furthermore, age, gender, mothers working a 15-hour day, mother’s educational level, parental divorce rates, parental death, and family monthly income predicted therapy outcomes. Conclusion: Results provide support for the effectiveness of eclectic art and CBT to improve children’s mental health and reduce anxiety through changing thoughts, beliefs, emotions, and behaviors that may cause fear and anxiety. © 2017, Sociedade de Psiquiatria do Rio Grande do Sul. All rights reserved.